Perception of Female Students towards Social Media-Related Crimes. - Ghazali, Suriati; Ghani, Norhayati Mat (Pertanika Journal of Social Sciences & Humanities, 2018)
Various social media platforms such as Facebook, YouTube and WhatsApp are often used by youths today to socialise, entertain themselves and to obtain the latest news. However, it has also led to rampant crimes. The objective of this paper is to investigate the perceptions of Malaysian female university students on social media crimes. Sixty female undergraduate students from Universiti Sains Malaysia were selected as respondents using simple random and convenient sampling. Meanwhile 10 of them were chosen for in-depth interviews. All respondents have social media accounts such as Facebook, Instagram, Twitter and WhatsApp. Majority of them were aware of crimes involving social media, however only 28% of them decided to limit their usage of social media due to concerns of becoming a potential victim. Meanwhile, 72 per cent use social media without any limitation. This study contributes to the knowledge of perceptions of young women at Malaysian universities and their vulnerability to social media crimes. It is suggested relevant bodies should take into account the possible dangers that can be generated from social media which can affect the psychological health of young women.